KONDISI EKONOMI MASYARAKAT AKIBAT PERUBAHAN USAHA INDUSTRI PERKAYUAN MENJADI PERKEBUNAN KELAPA SAWIT (Elaeis guineensis jacq) DESA SUNGAI ASAM KABUPATEN KUBU RAYA - Zainudin, Zainudin; Roslinda, Emi; Dewantara, Iswan (Universitas Tanjungpura, 2020)
The national plywood industry is declining, 6ut of the 100 existing wilt plywood companies, only 40% are still active. Many plywood companies have closed due to difficulties in obtaining raw materials and increased production costs due to the global crisis..The purpose of this study is to examine the economic condition of the community due to changes in land use into oil palm plantations. This research is located in Sungai Asam Village, Kubu Raya Regency. Purposive sampling is taken. Data analysis uses household level income analysis. The analysis uses survey techniques and direct interviews to respondents. The results of the expansion of oil palm plantations have given a change to the Sungai Asam community, which has had an impact on the economy of the communities surrounding the plantations. The expansion of oil palm plantations in Sungai Asam Village, Sungai Raya district, Kubu Raya Regency, has given a change to the community, where this change has an impact on the economic conditions of the communities around the plantation. The reduction in land area that occurred before the expansion was 15.437 Ha after the expansion to 6.435 Ha, the reduction of the land occurred, whereas on the contrary the community owned before and after the expansion was reduced but not significant. Income changes occurred before the expansion of income, which was originally Rp 1,286,011,992 / year, after the expansion to Rp 1,244,443,992 / year.Keyword : Change, Impact, Income